A series active power filter adopting hybrid control approach. - Zhaoan Wang (IEEE Transactions on power electronics)
The series active power filter (APF) is suitable for compensating a voltage type harmonics-producing load, whereas the control approach it adopts may directly influence its compensation characteristics. This paper first discusses the control approach of detecting source current in terms of the basic operation principle of a series APF, then developing a control approach of detecting load voltage. On the basis of these, a hybrid control approach is proposed. In this approach, the reference signal of the compensation voltage needed by the series APF is obtained by detecting both source current and load voltage. Thus, this approach has the advantages of the first and the second control approaches and, at the same time, it can overcome their respective drawbacks. For practical realization, the control methods of the PWM inverter in the series APF and for regulating its DC side voltage are discussed in detail. A prototype of the series APF is manufactured and corresponding experimental investigation is done. The results show that when the series APF, if adopting the hybrid control approach instead of the other two, compensates for the voltage type harmonics-producing load, its performance can be improved greatly